Kajian Pengelolaan Keuangan Organisasi (Studi Kasus Terhadap PT Aviasi Pariwisata Indonesia Pasca Pandemi Covid 19) - Kurniasari, Erika; Hindriyani Astuti, Nur Afifah; Marwiyah, Siti; Sugiyono, Sugiyono (JAF (Journal of Accounting and Finance), 2024)
This research was conducted with the aim of examining the financial management performance of one company in the tourism sector, namely PT Aviasi Wisata Indonesia from the 2020-2022 period, which was carried out using various analyses, namely using Profitability Ratios, Solvency Ratios and Liquidity Ratios. The tourism sector is one of the sectors that is of concern to the government because it is able to make a large contribution to the country's foreign exchange. However, since the Covid-19 pandemic, the tourism sector has plummeted due to restrictions and even closure of tourist travel. Therefore, this research was conducted to find out whether there was an influence of these problems on the financial management performance of PT Aviasi Wisata Indonesia. This research uses a quantitative approach with case study methods and descriptive data analysis. The results of research using profitability ratios show that the company's ability to generate profits has increased, using solvency ratios shows that the company's ability to fulfill all its liabilities has increased, apart from that, calculations using liquidity ratios show that the company's ability to pay off short-term obligations has increased. Overall, the company's financial performance in 2022 has increased, although not yet significantly. Recommendations for further research are that research needs to be carried out with a wider scope so that it can describe the condition of financial management in the tourism sector as a whole. Keyword: Liquidity Ratio; Performance; Profitability Ratio; Solvency Ratio; Tourism Sector